The seal of the sanga : on the old Babylonian sangas of Šamaš of Sippar-Jaḫrūrum and Sippar-Amnānum - Tanret, Michel. (Cuneiform Monographs, 2010)
This study assembles and examines all available documentation on the first and second sangas of Šamaš of the Ebabbar temple in Old Babylonian Sippar as well as on those in the Edikuda temple in neighbouring Sippar-Amnānum. Their succession, family links and the length of their careers are discussed and newly completed drawings of their seals are provided, described and analyzed. The author addresses the evolving patterns of sealing and the changes in the seal legends, which yield information on the growing influence of the Marduk circles and thus of the kings of Babylon. The seal stones have been reconstructed from the impressions and conclusions are drawn concerning the choice of seal scenes by the different sangas as well as the use of family seals.